THE OOYS' COHPANIES 1599-1610: A DISCUSSION OF ACTING STYLE - Bennett, Susan (My University, 1983)
This thesis examines the boys' theatre companies with particular emphasis upon the most commercial phase of their history.
Boy actors, however, had been part of English dramatic tradition for several centuries prior to the 1599-1610 period, and their stage history is discussed to illustrate the long-established features of their acting, as well as the companies' economic and social background.
The revival of the boys' companies around 1599 is given special attention as, at this time, the two main companies emerged as almost fully commercial concerns. This section also discusses the more diverse audience these companies were now attracting at the Paul's and Blackfriars theatres, and how such audiences shaped plays and performance.
In order to consider a theory of acting style, a wide selection from the boys' repertory has been examined, and, from this examination, a number of common aspects emerged. These were songs and music, visual effects, emphasis on women and romance, and virtuoso performance. A number of plays, discussed in close detail, discuss the specific nature of performance by the boys.
In general, the thesis considers the strengths and weaknesses of the boys' acting and finally considers the reasons for the companies' demise around 1610.
Keywords: English Language and Literature; English Language and Literature